1997
DOI: 10.1016/s0002-9394(14)71725-8
|View full text |Cite
|
Sign up to set email alerts
|

Corneal infiltration after recurrent corneal epithelial erosion

Abstract: Aims-To describe the clinical features of patients with a history of recurrent corneal epithelial erosion who develop acute corneal infiltration. Methods-The records were reviewed of patients who had previously been examined and treated for recurrent corneal epithelial erosion and who presented again with signs suggestive of a microbial keratitis. Results-11 patients were described; one patient presented with similar signs on two occasions. There was typically a paracentral epithelial defect >2 mm in diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…3,14,15 The majority of acute corneal erosions occur within the lower half of the cornea, irrespective of the aetiology. 2 It has been suggested that recurrences occur in close proximity to the Hudson-Stahli line.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…3,14,15 The majority of acute corneal erosions occur within the lower half of the cornea, irrespective of the aetiology. 2 It has been suggested that recurrences occur in close proximity to the Hudson-Stahli line.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…10 These recurrent corneal erosions develop repeated corneal epithelial defects, which predispose to invasion by microbial agents. 11,12…”
Section: Discussionmentioning
confidence: 99%